The 2019 midterm elections in the Philippines: Party system pathologies and Duterte's populist mobilization. Issue 1 (March 2020) - Teehankee, Julio Cabral; Kasuya, Yuko
The May 13, 2019 midterm elections were generally seen as a referendum on the first three years of the presidency of Rodrigo R Duterte. The elections tested and consolidated the political strength of Duterte as the country's populist strongman president. Most of the national and local candidates he endorsed won their contests for the 18, 066 national and local positions. The election also resulted in a victory for the administration's nine senatorial candidates (out of 12 seats) and a majority of its governors, mayors, and local legislators. The results follow the historical patterns of midterm elections in the post-authoritarian period. But unlike previous Philippine presidents, Duterte did not personally endeavor to consolidate his political support under his dominant party solely through the systematic mobilization of patronage. Duterte eschewed patronage-based political party building in favor of populist mobilization or the rallying of mass supporters toward contentious political action with minimum institutional intermediation. With a record high trust rating, Duterte was not only an active endorser of candidates, but he was also both a staunch defender of his allies and a relentless attacker of the opposition. In the end, the biggest winners in the 2019 midterm elections were not the candidates but Duterte himself.